Diseño de una turbina hidráulica, para la generación de energía eléctrica, para la comunidad arhuaca de gamake ubicada en el municipio de Pueblo Bello, Cesar. (2024)
It is called the National Interconnected System (SIN), the integration and connection of main plants, generation equipment, regional and interregional distribution networks, which manage to supply electrical energy in a greater proportion to the Colombian population [1]. By 2017, according to the Inter-American Development Bank (IDB) [2], due mainly to the dispersion of municipalities, poor, and in some places non-existent transportation and transportation infrastructure, the SIN covered 34% of the national territory, in which is inhabited by 96% of the country's population. The 66% of those geographical areas of the national territory where the public electricity service is not provided through the SIN are known as Non-Interconnected Zones (ZNI) and the remaining 4% of the population resides in them, for the year 2021 this percentage was equivalent to 2 million Colombians.